PERSEPSI MASYARAKAT MINAHASA TENTANG PASAR “EXTREME” TOMOHON - MESRA, ROMI; Hidayat, Muhammad Fajar; Korlefura, Criezta; Tanaya, Anang Mulya (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
One of the most famous markets in the Minahasa-North Sulawesi area nationally and internationally is also known as local wisdom known as the "extreme" Tomohon Market. The most famous of this market is usually because the traders sell unusual animals which are generally wild animals and even animals that are protected in other areas such as snakes, monitor lizards, wild boars, bats, dogs, cats and many more animals " other extremes. In its development, if we ask what the opinion or perception of the Minahasa community is about the "extreme" Tomohon market, we will find various opinions, even many discussions about this difference of opinion have appeared on social media. The purpose of this study is to reveal the Minahasa community's perception of the "extreme" Tomohon market. The method used is a qualitative research method. The results of this study are; naming the market "extreme" is a tourism gimmick, it is called "extreme" pet food only for outsiders of Minahasa, some Minahasa people consider "extreme" food a primitive habit, eating animals is "extreme" a hereditary tradition of the Minahasa community, the Minahasa religion allows eating food "extreme", eating "extreme" animals as a symbol of strengthening kinship, demand and supply of "extreme" animals are balanced